Critical Naturalism: Replies to the Critics of the Manifesto - Federica Gregoratto; Heikki Ikäheimo; Emmanuel Renault; Arvi Särkelä; Italo Testa (Krisis, 2024)
In this paper, we comment and discuss the fifteen replies that interpret, solicit, problematize, and further develop our Critical Naturalism: A Manifesto (Krisis 42(1)), that have been published in Krisis 43(1). In the paper, we address four overarching topics that we see emerging from the replies: Histories and traditions of criticial naturalism; the relation between theory and praxis; the question of what is critical about critical naturalism; and finally the question of utopia. Additionally, we discuss three general types of attitudes that our critics take to the Manifesto.